Limits to photosynthesis: seasonal shifts in supply and demand for CO2 in Scots pine. Issue 3 (7th December 2021) - Stangl, Zsofia R.; Tarvainen, Lasse; Wallin, Göran; Marshall, John D.
Summary: Boreal forests undergo a strong seasonal photosynthetic cycle; however, the underlying processes remain incompletely characterized. Here, we present a novel analysis of the seasonal diffusional and biochemical limits to photosynthesis ( A net ) relative to temperature and light limitations in high‐latitude mature Pinus sylvestris, including a high‐resolution analysis of the seasonality of mesophyll conductance ( g m ) and its effect on the estimation of carboxylation capacity ( V C max ). We used a custom‐built gas‐exchange system coupled to a carbon isotope analyser to obtain continuous measurements for the estimation of the relevant shoot gas‐exchange parameters and quantified the biochemical and diffusional controls alongside the environmental controls over A net . The seasonality of A net was strongly dependent on V C max and the diffusional limitations. Stomatal limitation was low in spring and autumn but increased to 31% in June. By contrast, mesophyll limitation was nearly constant (19%). We found that V C max limited A net in the spring, whereas daily temperatures and the gradual reduction of light availability limited A net in the autumn, despite relatively high V C max . We describe for the first time the role of mesophyll conductance in connection with seasonal trends in net photosynthesis of P. sylvestris, revealing a strong coordination between g m and A net, but not between g m and stomatal conductance.